Minimum Age and Developmental Capabilities Indicating Readiness for Self-Administration with Home Health Care Devices of Varying Complexities: An Empirical Investigation and Quantitative Complexity Model - Bassock, Stephanie. (2017)
Abstract: As children develop, physically and cognitively, many of them strive for personal independence. For children diagnosed with chronic diseases, their desire to act independently might lead them to become involved in their own healthcare, performing diagnostic and therapeutic tasks using medical devices. This research identified a typical age at which children are more capable of performing tasks with home health care devices (i.e., blood glucose meters, nebulizers) with minimal error. In addition, this research evaluated the relation of child development and device complexity to the prevalence of use errors. Nine years of age emerged as a threshold at which a majority of children could perform medical device tasks with minimal error. Moreover, children's age and working memory capacity and device complexity accounted for a significant proportion of the variance in use error rate. Additionally, the researcher provided a method for quantifying device complexity as well as a metric for estimating the rate of potential for use errors by children.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Daniel Hannon.; Committee: Michael Wiklund, Donald Lombardi, and Margaret Morris.; Keywords: Developmental psychology, Health care management, and Engineering.